A Comment on Market Structure and Stabilization Policy - Meltzer, Allan H. (The Review of Economics and Statistics, 1958)
Recently, in this REVIEW (J. K. Galbraith, "Market Structure and Stabilization Policy,this REVIEW, XXXIX (May 1957) I24-33) Professor Galbraith has asserted that in the case of monetary policy the "inflation can be controlled by denying credit to what are, in a general way, the least powerful firms" (page 132). Elsewhere, these least powerful firms are identified as the smaller firms (pages 131, 132, 133), and evidence concerning the distribution of bank loans by size is presented, to indicate that "while the case cannot be proven, there is a strong probability that in the last couple of years the effect of monetary policy has been to ration credit from all sources away from smaller firms in the competitive sector and to larger firms in the oligopolistic sector" (page 133).